(untitled) (Latakia University Journal -Basic Sciences Series, 2014)
درسنا العوامل المؤثرة في تفاعل الاشتقاق لسيرين (Ser) وغلايسين (Gly) بمزيج من كاشفي الاشتقاق أورتوفتال ألدهيد (OPA) و3 مركبتو بروبيونيك أسيد (3-MPA)لتشكيل مشتقات ايزندولية،حددنا الزمن اللازم والأمثل لتفاعل الاشتقاق وهو خمس دقائق،يتم التفاعل في وسط من واقي البورات (pH=10,0.4M)، بنسبة ارتباط 3-MPA:OPA توافق 1:3 ونسبة ارتباط OPA:Amino acid توافق 1:2،حددنا الزمن الأمثل لقياس المركب المشتق من 0.1-20 min. وبعد دراسة كافة هذه العوامل قمنابتحديد المشتق الايزندولي للسيرين والمشتق الإيزندولي للغلايسين بالتحليل بالكروماتوغرافيا السائلة عالية الأداءبالاعتماد على كاشف الفلورة من أجل التحديد الكمي لـــ Ser, Gly، باستخدام العمود Agilent Zorbax Exclipe RP C18،وقياس الفلورة عندλEx= 340 nm)، (λEm= 450 nm. حصلناعلى مجال قياس خطي µM- 250.5من أجل Ser، 1 - 25 µM من أجل Gly ، وحساسية ودقةعاليتين،ويتبين ذلك من القيمة المنخفضة للانحراف المعياري النسبي المئوي RSD% الذي لم يتجاوز قيمته لأصغر تركيز محدد( 3.25% بالنسبة لــ Serو3.07% بالنسبة لــ Gly) ، وبنتائج صحيحة ودقيقة من خلال المردود النسبي المئوي%(103.0-102.0) بالنسبة لــ Ser و %(95.8-94.0) بالنسبة لــ Gly. بلغحد الكشف للسيرينnM36.82 وحد التحديد الكمي nM111.59و حد الكشف للغلايسين 22.12 nM وحد التحديد الكمي nM67.02. We studied the Necessary Factors effecton Derivatization reaction forSerine and Glycine, The method involves the derivatization of Serine andGlycinewith a mixture of O-Phthaldialdehyde/3-Mercaptopropionic acid reagents to formisoindole derivative. The optimum time reaction was 5 min, in borate buffer (pH=10,0.4M), at molar ratio 3-MPA:OPA/1:3 and OPA:Amino acid/ 1:2, The optimum time for measurement was 0.1-20min. After the Derivatization step we determine isoindole derivatives with High Performance Liquid Chromatographyutilizing afluorescence (FL) detector for reliable quantitative determination of (Ser and Gly).The chromatographic separation was achieved on a reversed-phase Agilent Zorbax Exclipe RP18 (C18). The FL detector was set at excitation wavelength(λEx) of 340 nm and emission wavelength (λEm) of 450 nm. This method was validated with respect to linearity,0.5 – 25 µMfor Ser, and1 – 25 µMfor Gly, highly sensitivy, accuracy and precision with RSD% was not more than3.25 %, 3.07% for Ser and Gly respectively.And recovery% was (102.0-103.0)% for Ser, (94.0-95.8)% for Gly.The calculated detection limit was very low (36.82, 22.12) nMfor Ser and Gly, and with very low LOQ (111.59, 67.02)nMfor Ser and Glyrespectively.